Vagus nerve stimulation parameters evoke differential neuronal responses in the locus coeruleus. Issue 5 (10th March 2023) - Farrand, Ariana; Jacquemet, Vincent; Verner, Ryan; Owens, Misty; Beaumont, Eric
Abstract: Vagus nerve stimulation (VNS) is used to treat drug‐resistant epilepsy and depression, with additional applications under investigation. The noradrenergic center locus coeruleus (LC) is vital for VNS effects; however, the impact of varying stimulation parameters on LC activation is poorly understood. This study characterized LC activation across VNS parameters. Extracellular activity was recorded in rats' left LC while 11 VNS paradigms, utilizing variable frequencies and bursting characteristics, were pseudorandomly delivered to the left cervical vagus for five cycles. Neurons' change from baseline firing rate and timing response profiles were assessed. The proportion of neurons categorized as responders over 5 VNS cycles doubled in comparison to the first VNS cycle ( p  < 0.001) for all VNS paradigms, demonstrating an amplification effect. The percentage of positively consistent/positive responders increased for standard VNS paradigms with frequencies ≥10 Hz and for bursting paradigms with shorter interburst intervals and more pulses per burst. The synchrony between pairs of LC neurons increased during bursting VNS but not standard paradigms. Also, the probability of evoking a direct response during bursting VNS was higher with longer interburst intervals and a higher number of pulses per burst. Standard paradigms between 10–30 Hz best positively activates LC with consistency to VNS while the best bursting paradigm to increase activity was 300 Hz, seven pulses per burst separated by 1 s. Bursting VNS was effective in increasing synchrony between pairs of neurons, suggesting a common network recruitment originating from vagal afferents. These results indicate differential activation of LC neurons depending on the VNS parameters delivered. Abstract : The percentage of positively consistent/positive responders increased for standard VNS paradigms with frequencies ≥ 10Hz and for bursting paradigms with shorter interburst intervals and more pulses per burst. Bursting VNS was effective in increasing synchrony between pairs of neurons, suggesting a common network recruitment originating from vagal afferents. These results indicate differential activation of LC neurons depending on the VNS parameters delivered.